Synthesis and Characteristic of Precipitated Nano-Silica - Sadeghi, Mohammad; Dorodian, Mahboubeh; Rezaei, Masoumeh (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The reaction of precipitation of amorphous silicon dioxide from aqueous solution of sodium silicate and sulfuric acid has been studied. The factors affecting the precipitation process of the sodium silicate solution such as sodium silicate concentration and addition of anionic surfactant (sodium dodecyl sulfate, SDS) on particle size, size distribution and degree of agglomeration of the precipitated silica were examined. The precipitation of silica from the produced sodium silicate solution was carried out using sulfuric acid at pH 7. Scaning electron microscope (SEM), transmission electron microscope (TEM) and Dynamic light scattering (DLS) have been used for characterization of the produced nano-silica. The surface area of silica was tested by oil absorption method according to ASTM standard. Results showed that the particle size of the precipitated silica gel was decreased with increasing Na2SiO3 and SDS concentrations and Particle size of about 44nm can be achieved at 20% Na2SiO3 and 200ppm SDS. But with decreasing particle size, degree of agglomeration also increased.